A piezoelectric smart backing ring for high-performance power generation subject to train induced steel-spring fulcrum forces. (1st April 2022) - Wang, Jianjun; Cao, Yalei; Xiang, Hongjun; Zhang, Zhiwei; Liang, Junrui; Li, Xin; Ding, Deyun; Li, Teng; Tang, Lihua
Graphical abstract: Highlights: A smart backing ring used in steel-spring isolators is developed with energy harvesting ability. The developed harvester can easily achieve a maximum power output in the order of 100 mW. The proposed harvester design can achieve the power output in the order of 1 W after structural optimization. A self-powered wireless sensing system is realized for railway applications. Abstract: Long-term monitoring of the vertical displacement and the service status of the steel springs is critically important to ensure the operation safety of the railway. However, powering the monitoring system is still a challenging issue. To address this issue, a piezoelectric smart backing ring is designed and fabricated for harvesting the kinetic energy induced by the fulcrum force in the steel-spring isolators by passing trains. The fabricated prototype mainly consists of a concave-shaped hollow base, a convex-shaped hollow cover plate, and twelve piezoelectric stacks. The energy harvesting performance of the fabricated prototype under the harmonic force and the steel-spring fulcrum force is evaluated experimentally and theoretically. Effects of key factors, such as forcing amplitude and frequency, and parameters of piezoelectric stacks on the harvester's performance are analyzed and discussed. The results show that the maximum average power of the fabricated prototype can reach up to 500 mW under the actual steel-spring fulcrum force levels. Furthermore, by designing the proper piezoelectric stack radius and proper piezoelectric stack number, the maximum average power can reach up to the order of 1 W. It is evaluated that the prototype is used to harvest the total energy of about 12.74 J per day from the steel-spring fulcrum force induced by passing trains, while for a continuous rail transit rigid bridge with 36 blocks of floating concrete slabs including 1008 steel-spring isolators, the harvested total energy per day can reach up to about 12.84 kJ. Finally, a self-powered wireless temperature sensing system based on the proposed harvester is developed, demonstrating the feasibility of the implementation of service status monitoring of the steel springs and the health status monitoring of the railway bridges by energy harvesting.